2010
DOI: 10.1021/jf904593n
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Xanthine Oxidase Inhibitory Effects of Extracts and Main Polyphenolic Compounds Obtained from Geranium sibiricum L.

Abstract: The antioxidant capacity and xanthine oxidase inhibitory effects of extracts and main polyphenolic compounds of Geranium sibiricum were studied in the present work. The antioxidant capacity was evaluated by ferric reducing antioxidant power, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, superoxide radical scavenging, nitric oxide scavenging, beta-carotene-linoleic acid bleaching, and reducing power assays. Among the extracts and four fractions, the ethyl acetate fraction showed the highest phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 28 publications
2
69
0
Order By: Relevance
“…Several studies have demonstrated that geraniin suppresses lung cancer by inhibiting the TGF-β1-induced epithelial-mesenchymal transition [14], exerts a protective effect against osteoporosis in ovariectomized rats [15], and inhibits the chaperone activity of Hsp90 thus providing a multi-targeted approach against cellular oncogenic processes [16]. In our previous studies, geraniin showed efficient radical scavenging activities, including scavenging of superoxide and DPPH radicals, as well as an excellent reducing power [17]. Another one of our studies revealed that geraniin had the ability to reduce H 2 O 2 -induced cell death in vitro by activating Nrf2 signaling [18].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have demonstrated that geraniin suppresses lung cancer by inhibiting the TGF-β1-induced epithelial-mesenchymal transition [14], exerts a protective effect against osteoporosis in ovariectomized rats [15], and inhibits the chaperone activity of Hsp90 thus providing a multi-targeted approach against cellular oncogenic processes [16]. In our previous studies, geraniin showed efficient radical scavenging activities, including scavenging of superoxide and DPPH radicals, as well as an excellent reducing power [17]. Another one of our studies revealed that geraniin had the ability to reduce H 2 O 2 -induced cell death in vitro by activating Nrf2 signaling [18].…”
Section: Introductionmentioning
confidence: 94%
“…Gallic acid (3,4,5-triphydroxyl-benzoic acid; GA) as a naturally occurring plant phenol is one of the major bioactive compounds isolated from water caltrop [2,3,4,5]. Various pharmacological activities of GA have been reported, including anti-inflammatory, antiatherosclerotic, anticarcinogenic, and antioxidant activities[6,7,8,9], etc. Studies have also demonstrated that GA selectively induced cancer cell death by apoptosis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the EtOH extracts of the stem bark and leaves as well as the aqueous extracts of the leaves exhibited stronger DPPH radicals quenching ability with lower IC 50 values than trolox. The computed IC 50 values for the EtOH extract of the stem bark (1.37 µg/ml) and aqueous extract of the leaves (1.83 µg/ml) are especially remarkable because only a few authors (Wu et al, 2010) reported such low IC 50 values as found with these extracts in spite of hundreds of reports on the DPPH radical scavenging activity of extracts from plants in different parts of the world. This result could further indicate that these extracts contain powerful free radical scavenging phytochemicals that might have the ability to inhibit free radical upsurge as well as OS and therefore could be useful therapeutic agents for treating radical-related pathological changes.…”
Section: Discussionmentioning
confidence: 99%